Genetic and molecular characterization of the human Osteosarcoma 3AB‐OS cancer stem cell line: A possible model for studying osteosarcoma origin and stemness12. Issue 6 (25th February 2013) - Di Fiore, Riccardo; Fanale, Daniele; Drago‐Ferrante, Rosa; Chiaradonna, Ferdinando; Giuliano, Michela; De Blasio, Anna; Amodeo, Valeria; Corsini, Lidia R.; Bazan, Viviana; Tesoriere, Giovanni; Vento, Renza; Russo, Antonio
Abstract Finding new treatments targeting cancer stem cells (CSCs) within a tumor seems to be critical to halt cancer and improve patient survival. Osteosarcoma is an aggressive tumor affecting adolescents, for which there is no second‐line chemotherapy. Uncovering new molecular mechanisms underlying the development of osteosarcoma and origin of CSCs is crucial to identify new possible therapeutic strategies. Here, we aimed to characterize genetically and molecularly the human osteosarcoma 3AB‐OS CSC line, previously selected from MG63 cells and which proved to have both in vitro and in vivo features of CSCs. Classic cytogenetic studies demonstrated that 3AB‐OS cells have hypertriploid karyotype with 71–82 chromosomes. By comparing 3AB‐OS CSCs to the parental cells, array CGH, Affymetrix microarray, and TaqMan® Human MicroRNA array analyses identified 49 copy number variations (CNV), 3, 512 dysregulated genes and 189 differentially expressed miRNAs. Some of the chromosomal abnormalities and mRNA/miRNA expression profiles appeared to be congruent with those reported in human osteosarcomas. Bioinformatic analyses selected 196 genes and 46 anticorrelated miRNAs involved in carcinogenesis and stemness. For the first time, a predictive network is also described for two miRNA family (let‐7/98 and miR‐29a, b, c) and their anticorrelated mRNAs (MSTN, CCND2, Lin28B, MEST, HMGA2, and GHR), which may represent new biomarkers for osteosarcoma and may pave the way for the identification of new potential therapeutic targets. J. Cell. Physiol. 228: 1189–1201, 2013. © 2012 Wiley Periodicals, Inc.